Implementation of "Room of Batik" Android Game Design - Sigit winarso; Joko Priono; Wilhelmus Filianto (Jurnal Indonesia Sosial Teknologi, 2024)
The Batik motif is one of its main characteristics. From this point on, the creation of a game based on a strategy to restore confidence in the previously lost batik. Based on the aforementioned curriculum, "Perancangan Game "Room Of Batik" Berbasis Android Sebagai Media Pembelajaran Batik" was created. It is hoped that games with a batik theme can enliven young people and increase their interest in local customs, particularly batik. This game will be developed using the Unity game engine and will be targeted at the Android platform, which is now the most widely used platform. The purpose of this platform's use is to increase gameplay among more people, hence increasing the number of users who may access the relevant game.